Effect of planting time and spacing on growth characteristics of yellow lantern chilli (Capsicum chinense) - MOIRANGTHEM, SANJU SINGH; GOGOI, SAILEN; FIYAZ, R ABDUL; RAMYA, K T; THONGBAM, PREMILA DEVI (The Indian Journal of Agricultural Sciences, 2012)
Yellow lantern chilli [(Capsicum chinense (Jacq.)], the world’s hottest chilli is mostly grown in the north eastern part of India. The crop is cultivated by traditional ways since time immemorial. However, very little research towards scientific cultivation has been conducted in the past and until now scientific package of practices is not available. In the present investigation, the effect of various planting time and spacing on the growth characteristics of the hottest chilli, yellow rantern chilli (bhoot jolokia) was studied in north-eastern hill region of India. Seeds of the variety local cultivar, bor Bhoot of bhoot jolokia were planted in four different dates i e September 15 (P1), October 15 (P2), January 15 (P3) and February 15 (P4) with three spacings viz. 75cm × 75cm (S1), 90cm × 90cm (S2) and 105cm × 105cm (S3). The results revealed that the growth parameters and yield attributing characters were significantly influenced by different planting dates and spacings. Sowing in September 15 (P1) and with a spacing 105cm × 105cm (S3) were recorded the highest plant height, number of primary branches, number of fruits/plant, fruit weight and fruit yield/plant. In case of phyllochron index September 15 sowing showed maximum days to phyllochron but closest spacing 75cm × 75cm showed maximum phyllochron. Among all the treatments, the crop sown in September with a spacing of 105cm × 105cm showed better performance for all the parameters studied and can be considered basis for studying the effects of other agronomic practices.